Dukungan Keterampilan Guru dalam Pembelajaran, Kelengkapan Fasilitas dan Kedisiplinan Terhadap Motivasi Belajar Siswa Mts Negeri Bekonang - Astuti, Tri Dwi; Fathoni, Ahmad (Manajemen Pendidikan, 2018)
The purpose of this study is to analyze and test teacher support skills in learning,completeness of learning facilities and learning discipline towards student learningmotivation. The population in this study were eighth grade students totaling 242students. The sample in this study were 151 students. Sampling using proportionalrandom sampling technique. Data collection techniques with questionnaires. Dataanalysis techniques with linear regression analysis. The results of this study indicatethat there is support for teachers ‘skills in teaching students’ learning motivation inMTs. Negeri Bekonang as evidenced by the value of the β coefficient of 0.328 witha significant value of 0.000 <0.05. The existence of learning facilities support forstudents’ learning motivation in MTs. Negeri Bekonang as evidenced by the value ofthe β coefficient of 0.269 with a significant value of 0.001 <0.05. The existence ofdisciplinary support for students’ learning motivation in MTs. Negeri Bekonang asevidenced by the value of the β coefficient of 0.265 with a significant value of 0.000<0.05.